ENVIRONMENTAL CONTENTS IN LAO LANGUAGE TEXTBOOKS OF ELEMENTARY SCHOOL - Rattana Chanthao (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The government of Lao PDR has a clear environmental policy which is specified in the national economic and social development plan. Therefore, environmental issues are included in the Laotian textbooks to raise environmental awareness among children at the elementary school level. This research is a qualitative research with documentary data in language area focusing on Lao language textbooks in Grade1-5. Content analysis was employed. The environmental issues are the physical environment and biological environment or organism. The results showed that there were 232 words in relation to the environment. There were 70 words about physical environment which can be classified into 30 hydrographic words, 21 climate words, and 19 topography words. In addition, there were 162 words in relation to biological environment or organism which can be categorized into 91 animal words and 71 plant words. In the animal word category, it is found that the most vocabulary found was about wildlife. In the plant word category, trees or perennials were mostly found. The physical environmental terminology related to hydrology is found, including water, rivers, swamps, and floods. Obviously, there were a large number of vocabulary about living things, including wildlife and trees. This reflects that the Lao language textbooks emphasize knowing, preserving, and paying attention to water resources, wildlife especially forests and rivers since childhood.